2022
DOI: 10.1093/jbcr/irac058
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Laryngotracheal Complications After Inhalation Injury: A Scoping Review

Abstract: Long-term laryngotracheal complications (LTLC) after inhalation injury (II) are an under-recognised condition in patients with burns. The purpose of this study was to systematically review all available evidence on LTLC after II and identify gaps in knowledge to guide the direction of future research. A scoping review was performed to synthesize all available evidence on LTLC after II, as guided by the question, “What are the LTLC after II, in patients with or without a history of translaryngeal intubation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Additionally, dysphonia negatively impacts quality of life, including social interactions, work performance, and pain [34]. A scoping review examining the long-term laryngotracheal complications after inhalation injury noted that dysphonia was a frequent sequela after injury [35]. Close monitoring and timely interventions to address dysphonia are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, dysphonia negatively impacts quality of life, including social interactions, work performance, and pain [34]. A scoping review examining the long-term laryngotracheal complications after inhalation injury noted that dysphonia was a frequent sequela after injury [35]. Close monitoring and timely interventions to address dysphonia are important.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that prolonged intubation can exacerbate the risk of vocal cord injury, thus emphasizing the potential benefits of minimizing the duration of intubation to mitigate voice quality complications [16]. Over the last two decades, many have debated the proper timing of tracheostomy for patients with prolonged mechanical ventilation [16,18,35]. The American College of Chest Physicians guidelines recommend considering a tracheostomy in patients receiving mechanical ventilation for more than 21 days [36,37].…”
Section: Discussionmentioning
confidence: 99%